THE IMPORTANCE OF ORGANIZING PHYSICAL ACTIVITIES IN APARTMENTS, IN INCREASING THE PHYSICAL ACTIVITY OF THE POPULATION (Proximus Journal of Sports Science and Physical Education, 2024)
this scientific article shows human health, the importance of physical education and sports in strengthening it, the attention given to it by the state, the decisions being made. The importance of physical activities organized in the apartments in ensuring the implementation of the decisions of the state being adopted, scientific analysis and conclusions and suggestions were made on the basis of the experiences achieved in this regard